DETECTION OF CRIMES USING UNSUPERVISED LEARNING TECHNIQUES - Babu, R. Buli; Snehal, G.; Kiran, Aditya Satya (APTIKOM Publisher, 2017)
Data mining can be used to detect model crime problems. This paper is about the importance of datamining about its techniques and how we can easily solve the crime. Crime data will be stored in criminal?s database.To analyze the data easily we have data mining technique that is clustering. Clustering is a method to group identicalcharacteristics in which the similarity is maximized or minimized. In clustering techniques also we have different typeof algorithm, but in this paper we are using the k-means algorithm and expectation-maximization algorithm. We areusing these techniques because these two techniques come under the partition algorithm. Partition algorithm is oneof the best methods to solve crimes and to find the similar data and group it. K-means algorithm is used to partitionthe grouped object based on their means. Expectation-maximization algorithm is the extension of k-means algorithmhere we partition the data based on their parameters.